Metasomatized mantle lithosphere and altered ocean crust as a fluid source for orogenic gold deposits. (1st October 2022) - Zhao, Hesen; Wang, Qingfei; Kendrick, Mark A.; Groves, David I.; Fan, Tao; Deng, Jun
Abstract: Whether auriferous hydrothermal fluid is generated during crustal metamorphism or by subcrustal processes to form orogenic gold deposits is hotly debated. Noble gas isotope and halogen abundance ratios can provide important constraints to help resolve this controversy. The Danba gold deposit is a rare example of a Jurassic age hypozonal orogenic gold deposit on the western margin of the Yangtze Craton, China. It is characterized by thick barren quartz veins with fractures infilled by thin auriferous quartz veinlets. The syn -gold quartz veinlets are associated with plagioclase and pyrrhotite and are distinguished from the barren quartz vein hosts on the basis of cathodoluminescence, trace-element content and Raman spectroscopy and microthermometry of fluid inclusions. The dominant fluid inclusions in the gold-bearing quartz and plagioclase are H2 O–CH4 with vapor fill of ∼ 15–45 vol% and high pressure-corrected trapping temperatures of ∼ 500 °C, low salinities (<4 wt% NaCl equiv.) and high Mg/Fe ratios. Crushing syn -gold quartz and plagioclase released fluid inclusions with 40 Ar/ 36 Ar ratios of between 490 and 710, molar Br/Cl ratios of (0.3–0.7) × 10 −3 and molar I/Cl ratios of (18–60) × 10 −6 . Crushing syn -gold pyrrhotite released fluid inclusions with 3 He/ 4 He ratios of 0.21–0.38 Ra (Ra = air value, 1.39 × 10 −6 ) that are higher than typical crustal values of < 0.1 Ra, and 40 Ar/ 36 Ar of 330–640 that are similar to the gold-related quartz-hosted inclusions. The combined noble gas and halogen data do not favor an auriferous fluid derived from K- and U-rich Proterozoic granitic basement, which is expected to have radiogenic 40 Ar/ 36 Ar and 3 He/ 4 He ratios. Instead, the data are more consistent with a fluid source from underlying mantle lithosphere containing a high proportion of altered ocean crust (AOC). The auriferous fluid that formed the Danba gold deposit is thus considered to have been derived from a source comprising both metasomatized mantle lithosphere that had been fertilized in a Neoproterozoic subduction event and a portion of relict AOC beneath the western margin of the Yangtze Craton. In contrast with syn -gold fluid inclusions, those in pre-gold barren quartz are H2 O–CO2 dominated. Crushing pre-gold quartz released fluid inclusions with 40 Ar/ 36 Ar ratios of 2410–5450, Br/Cl ratios of (1.2–1.5) × 10 −3 and I/Cl ratios of (60–80) × 10 −6 that are distinctly different to the gold-ore stage. The higher 40 Ar/ 36 Ar ratios of the pre-gold fluids are consistent with a source for the barren host quartz veins from prograde greenschist- to amphibolite-facies metamorphism of the Proterozoic granitic basement.